The relationship between theoretical concepts in electrodynamics and experimental activities: A study on students' citizenship training - Oliveira , Wilson Campos; Beranger, Juan Alberto (Seven Editora, 2024)
This article investigates the relationship between theoretical concepts in electrodynamics and experimental activities, focusing on the citizenship formation of students. Electrodynamics, a branch of physics that studies the movement of electrical charges in circuits, is often considered abstract and distant from everyday reality. The teaching of science, in particular electrodynamics, often faces the challenge of making theoretical concepts accessible and relevant to students, as well as promoting a citizenship education that prepares them to face the challenges of the contemporary world. In this context, the central question arises: how does the integration of experimental activities in the teaching of electrodynamics influence students' understanding of theoretical concepts, their ability to apply these concepts in everyday situations, and their development as critical and responsible citizens? The general objective is to: analyze how students relate theoretical concepts to experimental activities and everyday circumstances, collaborating for their citizenship formation and, specifically: to investigate the performance of experimental activities in electrodynamics; evaluate the students' application and analyze the impact of integration. The methodology adopted in this study was based on the application of data and used a qualitative method. UD (Didactic Units) were used, which consist of a series of orderly, structured and articulated activities, carried out to achieve the proposed objectives. Activities included oral reading of the dissemination text, group discussions, and knowledge tests. The results reveal that students need more interlocution to be able to develop with more intimacy to the knowledge of Physics and, as a conclusion, students interact with the systems. Activities whose accomplishment evidenced the investigation procedures and the way science is developed, socioeconomic-culturally contextualized, were provided with the opportunity to provide students with the appropriation of the procedures they used to create the numerous physical theories, in order to understand in the same way how science is done. DOI:https://doi.org/10.56238/sevened2024.010-003